Thermally Conductive Shape-Stabilized Phase Change Materials Enabled by Paraffin Wax and Nanoporous Structural Expanded Graphite - Yilin Zhao; Shuhui Huang; Zhaoguo Jin; Zhongnan Xie; Hong Guo; Haofeng Xie (Nanomaterials)
Paraffin wax (PW) has significant potential for spacecraft thermal management, but low thermal conductivity and leakage issues make it no longer sufficient for the requirements of evolving spacecraft thermal control systems. Although free-state expanded graphite (EG) as a thermal conductivity enhancer can ameliorate the above problems, it remains challenging to achieve higher thermal conductivity (K) (>8 W/(m·K)) at filler contents below 10 wt.% and to mitigate the leakage problem. Two preparations of thermally conductive shape-stabilized PW/EG composites, using the pressure-induced method and prefabricated skeleton method, were designed in this paper. The expanded graphite formed a nanoscale porous structure by different methods, which enhanced the capillary action between the graphite flake layers, improved the adsorption and encapsulation of EG, and alleviated the leakage problem. The thermal conductivity and the latent heat of the phase-change materials (PCM) prepared by the two methods mentioned above are 9.99 W/(m·K), 10.70 W/(m·K) and 240.06 J/g, 231.67 J/g, respectively, at EG loading by 10 wt.%, and the residual mass fraction was greater than 99% after 50 cycles of high and low temperature. In addition, due to the excellent thermal management capability of PW/EG, the operating temperature of electronic components can be stably maintained at 68–71 °C for about 15 min and the peak temperature can be reduced by at least 23 °C when the heating power of the electronic components is 10 w. These provide novel and cost-effective methods to further improve the management capability of spacecraft thermal control systems.